2011
DOI: 10.1126/science.1208686
|View full text |Cite
|
Sign up to set email alerts
|

A Main Group Metal Sandwich: Five Lithium Cations Jammed Between Two Corannulene Tetraanion Decks

Abstract: Lithium-coordinated polyaromatic anions such as tetrareduced corannulene, C(20)H(10)(4-) (1(4-)), are useful substrates to model and ultimately improve the graphitic electrodes in lithium-ion (Li(+)) batteries. Previous studies suggested that 1(4-) forms dimers encasing four Li(+) ions in solution. Here, we report a single-crystal x-ray diffraction analysis confirming the formation of a sandwich-type supramolecular aggregate with a high degree of alkali metal intercalation. In contrast to the prior model, our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
148
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 222 publications
(167 citation statements)
references
References 36 publications
14
148
0
1
Order By: Relevance
“…12 We have also demonstrated that the triple-decker supramolecular aggregate, [Li 5 (C 20 H 10 4– ) 2 ] 3– , can be crystallized in different external coordination environments, showing no significant effect on the geometry of the sandwich core. 11,13 In addition, the formation of the [Li 5 (C 20 H 10 4– ) 2 ] 3– product (abbreviated as Li 5 below) is confirmed in solution based on the observed shifts for sandwiched Li + ions (–11.70 ppm) and a proper 3 : 5 integration of external vs. internal ions in the 7 Li NMR spectra. Importantly, these results illustrated the ability of tetrareduced corannulene to engage all of its adjacent six-membered rings in alkali metal binding and thus to encapsulate a large amount of Li + ions, which can be related to the high charge capacity of the corannulene-based electrodes in Li-ion batteries.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…12 We have also demonstrated that the triple-decker supramolecular aggregate, [Li 5 (C 20 H 10 4– ) 2 ] 3– , can be crystallized in different external coordination environments, showing no significant effect on the geometry of the sandwich core. 11,13 In addition, the formation of the [Li 5 (C 20 H 10 4– ) 2 ] 3– product (abbreviated as Li 5 below) is confirmed in solution based on the observed shifts for sandwiched Li + ions (–11.70 ppm) and a proper 3 : 5 integration of external vs. internal ions in the 7 Li NMR spectra. Importantly, these results illustrated the ability of tetrareduced corannulene to engage all of its adjacent six-membered rings in alkali metal binding and thus to encapsulate a large amount of Li + ions, which can be related to the high charge capacity of the corannulene-based electrodes in Li-ion batteries.…”
Section: Introductionmentioning
confidence: 88%
“…10 However, structural investigations of the charged π-bowls were lagging behind their solution spectroscopic studies until we have accomplished the first X-ray diffraction characterization of the product formed by the tetrareduced corannulene with lithium counterions. 11 The formation of a remarkable aggregate with a Li 5 -core sandwiched between two C 20 H 10 4– decks has been established (Scheme 2a). This supramolecular aggregation with lithium ions allows to achieving a tetrareduced state of corannulene, as the electrochemical generation of C 20 H 10 4– cannot be accomplished due to a very large negative standard potential located outside of the current experimental window.…”
Section: Introductionmentioning
confidence: 99%
“…These curved polyarenes (often called p-bowls) are excellent electron acceptors, comparable to planar PAHs [1,2] and fullerenes [3,4], and could serve as key anode components in rechargeable Li-ion batteries. Corannulene, the smallest non-planar fragment of C 60 fullerene [5,6], was shown to exhibit high degree of lithium intercalation upon step-wise reduction [7][8][9][10] and corannulene-based anode materials have demonstrated a high reversible lithium capacity, almost twice as high as that of fully lithiated graphite [11,12]. The family of p-bowls also provides a natural platform for designing new organic materials with applications in light emitting-diodes [13][14][15][16], field-effect transistors [17][18][19], or photovoltaic cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…[9,11,18] On the contrary, while the formation of four-fold reduced corannulene was clearly observed in the reaction mixture with Li and K metals, the assignment of the specific products in solution was problematic. Notably, a shorter reaction time was observed for the mixed Li/K system compared to the Li-only reduction, pointing to a synergism of two metals.…”
Section: Dedicated To Professor Roald Hoffmann On the Occasion Of Hismentioning
confidence: 86%
“…[9] While the supramolecular aggregation of corannulene anions has been extensively investigated by the groups of Scott and Rabinovitz using solution NMR spectroscopy, [6a, 7-9, 10] structural identification of the resulting products in the solid state was lagging behind until 2011, when we have accomplished the first crystallographic characterization of the aggregate formed by the highly reduced corannulene with lithium counterions (Scheme 1). [11] A remarkable supramolecular structure with five lithium ions sandwiched between two four-fold reduced corannulene decks has been revealed.…”
Section: Dedicated To Professor Roald Hoffmann On the Occasion Of Hismentioning
confidence: 99%